2015
DOI: 10.1186/s40623-015-0352-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-volcanic crustal movements of the northernmost Philippine Sea plate detected by the GPS-acoustic seafloor positioning

Abstract: Repeatedly performing the GPS-acoustic seafloor positioning, we first succeeded in detecting non-volcanic seafloor movements on the Philippine Sea plate (PHS) subducting along the Sagami Trough. At a seafloor geodetic site on the northernmost part of the PHS off the Boso Peninsula, we detected significant eastward motion with respect to the central part of the PHS. This is unaccountable by the coupling between the Pacific plate and the PHS along the Izu-Bonin (Ogasawara) Trench because it would cause the westw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…• Seafloor crustal deformation measurements were performed at two stations along the Nansei-Shoto (Ryukyu) Trench, Japan • Strong interplate coupling was estimated from our measurements, whereas it had been thought to be weak at the Nansei-Shoto Trench • The coupled segment coincides with the source area of the 1791 event and is isolated from the area of short-term slow slip activity crustal deformation has been carried out with an observation network spanning from the Japan Trench to the Nankai Trough (Fujita et al, 2006;Kido et al, 2011;Sato et al, 2013Sato et al, , 2011Tadokoro et al, 2012;Tomita et al, 2017;Watanabe et al, 2015;Yokota et al, 2015). Interplate coupling states have been derived from the monitoring results of seafloor crustal deformation in the whole Nankai Trough subduction zone (Nishimura et al, 2018;Yokota et al, 2016) and for improving tsunami scenarios (Watanabe et al, 2018).…”
Section: 1029/2018gl078655mentioning
confidence: 95%
See 1 more Smart Citation
“…• Seafloor crustal deformation measurements were performed at two stations along the Nansei-Shoto (Ryukyu) Trench, Japan • Strong interplate coupling was estimated from our measurements, whereas it had been thought to be weak at the Nansei-Shoto Trench • The coupled segment coincides with the source area of the 1791 event and is isolated from the area of short-term slow slip activity crustal deformation has been carried out with an observation network spanning from the Japan Trench to the Nankai Trough (Fujita et al, 2006;Kido et al, 2011;Sato et al, 2013Sato et al, , 2011Tadokoro et al, 2012;Tomita et al, 2017;Watanabe et al, 2015;Yokota et al, 2015). Interplate coupling states have been derived from the monitoring results of seafloor crustal deformation in the whole Nankai Trough subduction zone (Nishimura et al, 2018;Yokota et al, 2016) and for improving tsunami scenarios (Watanabe et al, 2018).…”
Section: 1029/2018gl078655mentioning
confidence: 95%
“…The system employs GNSS (Global Navigation Satellite System) measurement of ship position and the precise acoustic ranging with an ultrasonic wave between the ship and seafloor acoustic transponders. Long‐term monitoring of seafloor crustal deformation has been carried out with an observation network spanning from the Japan Trench to the Nankai Trough (Fujita et al, ; Kido et al, ; Matsumoto, Ishikawa, et al, ; Sato et al, , ; Tadokoro et al, ; Tomita et al, ; Watanabe et al, ; Yokota et al, ). Interplate coupling states have been derived from the monitoring results of seafloor crustal deformation in the whole Nankai Trough subduction zone (Nishimura et al, ; Yokota et al, ) and for improving tsunami scenarios (Watanabe et al, ).…”
Section: Introductionmentioning
confidence: 99%
“… Ref. 18 suggested that our network had recorded the inter-seismic coupling process along the Sagami Trough.…”
Section: Background and Summarymentioning
confidence: 96%
“…The procedure for correcting for the displacement caused by the Tohoku-oki earthquake and estimating the secular velocities were explained in detail in Yokota et al (2016) and Graduate School of Environmental studies, Nagoya University (2016). We also used the published velocity for two stations in the easternmost part of the Nankai Trough ( Yasuda et al, 2014) and at two stations along the Sagami trough (Watanabe et al, 2015 before the Tohoku-oki earthquake. After transforming the secular velocities with the MORVEL (mid-ocean ridge velocity) Euler vectors (DeMets et al, 2010), which were used to realize the reference frame in Yokota et al (2016), offshore GPS-A and on-land GNSS velocities are plotted in Figure 1 in a common reference frame fixed to the Eurasian plate.…”
Section: Gps-a Velocity Datamentioning
confidence: 99%